PENGUJIAN PERTUMBUHAN DAN DAYA HASIL BEBERAPA GALUR TANAMAN CABE MERAH {Capsicum annuunft.) HASIL PERLAKUAN COLCHICINE - Joko R Witono (BERITA BIOLOGI, 1999)
This experiment aims to examine first generation (F1) of some lines of red pepper (taosicum ann'uum L) resulted by colchicine treatments,the examinatton covering growth and yield characters.The method was Randomized Complete Block Design (RCBD) with 16 lines resulted generation combination soaking time in colchicine solution (0, A 16, and 24 hours) and the red pepper varieties (Cipanas, Bengkulu, Jatilaba, and TIT super). The best growth character is 65, and the best yield character isG16.High heritability characters (height of plant, age of blossom, length of fruit, diameter of fruit, and weight of fruit) could be chosen for selection and plant breeding programs.